The performance of senior high school students on teacher-and-student-translated English verbal problems in mathematics - Almirol, Aida Almojuela 1955-
The main thrust of this research was to assess the performance of senior high school students on teacher- and student-translated English verbal problems in Mathematics. It also looked into the congruence between the translations of verbal problems by mathematics teachers and senior high school students, as well as the fidelity to the original version of the translated versions as shown by back translation technique.